Expression of Recombinant Antibody Fragment, Anti BNP-SCFV on the Periplasm of Escherichia Coli for the Detection of Heart Failure - Shabarni Gaffar; Sofyan Multazam N Aji; Yeni W Hartati; Safri Ishmayana; Toto Subroto (Universitas Jenderal Soedirman, 2017)
Basic natriuretic peptide (BNP) is a polypeptide hormone consist of 32 amino acids that secreted by the heart ventricle to respond the excessive stretching of heart muscle cells. BNP can be used as prognostic marker for patients with heart failure. The presence of BNP in blood can be detected by BNP antibody, which is anti BNP-single chain variable fragment (Anti BNP-SCFV). The antibody is a combination of polypeptides between varying region on the heavy chain (VH) and the light chain (VL) of immunoglobulin. Anti BNP-SCFV will bind to BNP through the antigen-antibody interaction. Concentration of BNP in a patientâs blood can be detected through the interaction of BNP with Anti BNP-SCFV using immunosensor method. Production of recombinant Anti BNP-SCFV in Escherichia coli as host is reported in the present study. Anti BNP-SCFV was expressed in fusion form with OmpC signal peptide that direct the protein to a periplasmic space. Expression was performed under RhaBad promoter as control using L-rhamnose as inducer. SDS-PAGE characterization showed consistent band at 28 kDa, which was assumed as Anti BNP-SCFV. The optimum expression was found at four hours after induction with 4 mM inducer. Anti BNP-SCFV was secreted from the cell as characterized by the presence of the protein on periplasmic membrane and extracellular fraction.